2015
DOI: 10.3109/0284186x.2015.1043396
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of acute toxicities during definitive chemoradiation using intensity-modulated radiotherapy for anal squamous cell carcinoma

Abstract: Purpose To identify clinical and dosimetric factors associated with acute hematologic and gastrointestinal (GI) toxicities during definitive therapy using intensity-modulated radiotherapy (IMRT) for anal squamous cell carcinoma (ASCC). Materials and methods We retrospectively analyzed 108 ASCC patients treated with IMRT. Clinical information included age, gender, stage, concurrent chemotherapy, mitomycin (MMC) chemotherapy and weekly hematologic and GI toxicity during IMRT. From contours of the bony pelvis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 18 publications
2
16
0
3
Order By: Relevance
“…Studies reporting the long-term outcome of IMRT reported either no or very rare incidence of Grade 3 or higher late sequelae [14,58,61,97,98,[129][130][131]. Three studies found only the gross tumor volume (GTV) dose to be predictive of acute Grade 2 GI toxicity [132][133][134]. A retrospective study showed a trend toward fewer late complications among the patients treated with a dose of <60 Gy: the late toxicity rate was 14% for a dose <60 Gy compared to 37% for a dose of !60 Gy (p ¼ .04) [36].…”
Section: Radiotherapy Technique and Dosage And Their Influence On Latmentioning
confidence: 99%
“…Studies reporting the long-term outcome of IMRT reported either no or very rare incidence of Grade 3 or higher late sequelae [14,58,61,97,98,[129][130][131]. Three studies found only the gross tumor volume (GTV) dose to be predictive of acute Grade 2 GI toxicity [132][133][134]. A retrospective study showed a trend toward fewer late complications among the patients treated with a dose of <60 Gy: the late toxicity rate was 14% for a dose <60 Gy compared to 37% for a dose of !60 Gy (p ¼ .04) [36].…”
Section: Radiotherapy Technique and Dosage And Their Influence On Latmentioning
confidence: 99%
“…The study of Mell et al [ 6 ] has revealed that white blood cell nadir is correlated with female gender, low BMI and lymph node positivity, and neutrophil nadir is correlated with female gender and low BMI. Moreover, it has been reported that ≥ Grade 2 leukopenia is associated with cycle number of chemotherapy, and ≥ Grade 2 neutropenia is associated with cycle number of chemotherapy and T stage [ 18 ]. Single factor analysis in the present has demonstrated that acute bone marrow suppression is not significantly associated with gender, age, BMI and clinical stage of rectal cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel: For rectal cancer patients, preoperatively treated with 3D-CRT, the absolute bowel volume receiving !15 Gy (V 15Gy ) has consistently been found to correlate with acute GI toxicity [7][8][9][10][11]. Studies of rectal [12], anal [13][14][15][16][17], prostate [18][19][20] and gynaecological [21][22][23] cancer patients treated with IMRT or arc therapy have found correlations between acute GI toxicity and dose levels from approximately 25-45 Gy, delivered in 25-28 fractions. For late GI toxicity in rectal cancer, the data is very limited.…”
Section: Literature Search: Oar Dose Levels For Lcrtmentioning
confidence: 99%